Investigation of the effect of SGLT-2 inhibitors on the triglyceride/glucose index in diabetic patients: a cross-sectional study - Karagöz Özen, Düriye Sıla; Kayabaş, Abdulcelil; İlhan Van, Rana; Demirağ, Mehmet Derya (The European Research Journal, 2025)
Objectives: The aim of this study is to estimate the change in the Triglyceride Glucose Index (TyG index), in patients with type 2 Diabetes Mellitus who are using a sodium-glucose cotransporter-2 (SGLT2) inhibitor, and to evaluate the effect of these drugs on triglyceride glucose index. Methods: This is a cross-sectional study of 55 diabetic patients in our internal medicine clinic in Turkey. Triglyceride, glucose, and glycosylated hemoglobin (HbA1c) values were measured at the beginning of the treatment and the 3rd-month follow-up. The TyG index of the patients before starting SGLT-2 inhibitor treatment and at the end of 3 months of treatment was calculated by the researchers using the data in the hospital digital records. Results: The mean age of 55 patients (56.4% male) was 62.7±10.2 years. The number of patients using dapagliflozin 10 mg was 15 (27.3%) and the number of patients using empagliflozin was 41 (72.8%). It was determined that fasting plasma glucose, TyG index, and HbA1c values before starting SGLT-2 inhibitor treatment and in the 3rd month of treatment decreased significantly (P